2021
DOI: 10.1103/physrevfluids.6.024502
|View full text |Cite|
|
Sign up to set email alerts
|

Active chaotic mixing in a channel with rotating arc-walls

Abstract: An active inline mixer suitable for flows at low Reynolds number and high Péclet number is studied. An alternated oscillatory forcing protocol is imposed by three rotating circular arc-walls in a straight channel. In the two-dimensional case, simple phenomenological arguments are used to estimate heuristically the mixing efficiency with two non-dimensional control parameters: the Strouhal number based on the bulk flow velocity, and the strength of the cross flow relative to the transport flow. The validity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 58 publications
5
16
0
Order By: Relevance
“…The previous study, presented in Ref. [18], helped to validate this new mixing concept. It has shown that the non-dimensional numbers that control the flow are: the Strouhal number St = W TU which represents the ratio of a characteristic time of the flow to the rotational period of the cylinders T, and the velocity ratio k = RW 0 U of the largest angular speed of the cylinders to the axial velocity of the flow.…”
Section: Working Fluid and Controlling Parametersmentioning
confidence: 81%
See 2 more Smart Citations
“…The previous study, presented in Ref. [18], helped to validate this new mixing concept. It has shown that the non-dimensional numbers that control the flow are: the Strouhal number St = W TU which represents the ratio of a characteristic time of the flow to the rotational period of the cylinders T, and the velocity ratio k = RW 0 U of the largest angular speed of the cylinders to the axial velocity of the flow.…”
Section: Working Fluid and Controlling Parametersmentioning
confidence: 81%
“…A detailed explanation of the choice of the rotational protocol of the cylinders is given in Ref. [18]. We have shown that the modulation of the angular velocities of the cylinders with a sine function and with opposite directions of rotation generate two flow topologies that alternate smoothly between each other.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover the least noisy tail is that of the MLLM (figure 4d), for which we have twice as much data as for the two other mixers, but that also corresponds to the more correlated mixer. Finally, note that El Omary et al [29] also found a t −3 tail when properly weighting their statistics.…”
Section: B Mixersmentioning
confidence: 88%
“…The matter further triggered a great amount of theoretical, numerical, or experimental works on the subject (see, for instance, Refs. [25][26][27][28][29][30][31][32][33]). Note finally that chaotic advection also applies for dynamical systems of higher dimension, as, for instance, 3D time-periodic flows [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%